Pengembangan Model Peer Counseling sebagai Media Pengalaman Praktik Konseling - muslikah, muslikah; hariyadi, sigit; amin, zakki nurul (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
Practical experience is an important component of counselor education program. Through the experience student counseling practice, counselor candidate  given the experience to apply the skills and knowledge they acquired in the lecture. Peer Counseling in this research defined as the involvement of youth in peer groups to provide particular input for the development of personality and social of adolescents. Thus, peer counseling can be utilized in the process of lectures, so counselors candidate can be optimized to obtain practical experience supervised by a professional counselor. This research aims to develop a peer counseling model as an experience counseling practice media in basic skills counseling subject. The design used is research and development. Subjects were students of BK FIP UNNES. Data collected through in-depth interviews, questionnaires and  document studies. Data analysis technique used is  interactive model of Miles and Huberman. Results of the research is a model of peer counseling as an experience counseling practice media in basic skills of counseling subject include: (a) rational, (b) Definition, (c) Interest, (d) assuming, (e) materials, (f) the stages of peer counseling implementation, (g) the evaluation and succes indicators, and function of group members, (h) the phase of the service, (i) the evaluation and follow-up. Based on  results expert validation obtained that the model is feasible and can be applied.